Mechanism simulation of oil displacement by imbibition in fractured reservoirs - Jing WANG; Huiqing LIU; Jing XIA; Yuetian LIU; Cheng HONG; Qingbang MENG; Yang GAO (Petroleum Exploration and Development, 2017)
Abstract: The mechanism model of both static and dynamic imbibition considering capillary pressure and gravity was presented based on the imbibition mechanisms and seepage theory. The validation of the model was performed using published experiment data. Then, this model was employed to study the impacts of oil viscosity, matrix permeability, core size, interface tension, and displacement rate on imbibitions. The results show that, the recovery decreases as oil viscosity increases, and the initial imbibition rate is much faster for lower viscosity oil. Imbibitions recovery is positively related to matrix permeability, the differences of oil recovery for low-permeability to tight oil reservoirs are obvious. Imbibitions effect is negatively related to core size. If the interface tension is low, imbibitions cannot occur without consideration of gravity. But it can occur even in very low interface tension scenario with consideration of gravity. On the whole, the recovery first increases and then decreases as the interface tension decreases. The gravity and capillary play different roles at different ranges of interface tension. There exists an optimal value range of displacement rate in fractured reservoir, which should be optimized with a sufficient oil production rate to achieve higher recovery. Key words: fractured reservoir, static imbibition, dynamic imbibition, imbibition mechanism, influencing factor